Ocena jakości usług świadczonych przez polskie kluby piłkarskie = Evaluation of the quality of services provided by the Polish football clubs - Dzięgiel, Andżelika; Luciński, Łukasz (Journal of Education, Health and Sport, 2015)
Dzięgiel Andżelika, Luciński Łukasz. Ocena jakości usług świadczonych przez polskie kluby piłkarskie = Evaluation of the quality of services provided by the Polish football clubs. Journal of Education, Health and Sport. 2015;5(11):516-532. eISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.35692 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2811%29%3A516-532 http://pbn.nauka.gov.pl/works/684758 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Original Text published © The Author (s) 2015. Dzięgiel Andżelika, Luciński Łukasz. Ocena jakości usług świadczonych przez polskie kluby piłkarskie. Quality in Sport. 2015;1(1):29-44. eISSN 2450-3118. http://ojs.ukw.edu.pl/index.php/QiS/article/view/QUALITY%20IN%20SPORT%201%20%281%29%202015%2C%20s.%2029-44 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport (null) 2391-8306 7 © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland. Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.11.2015. Revised 20.11.2015. Accepted: 30.11.2015. Andżelika Dzięgiel[1], Łukasz Luciński[2] Wydział Nauk Ekonomicznych i Zarządzana Uniwersytet Mikołaja Kopernika w Toruniu Ocena jakości usług świadczonych przez polskie kluby piłkarskie Evaluation of the quality of services provided by the Polish football clubs Streszczenie Kibice stanowią istotę dla widowiska sportowego, a ich brak na trybunach negatywnie wpływa na wartość imprez ocenianych z perspektywy fanów, sponsorów i mediów. Głównym celem badań była ocena jakości wybranych usług oferowanych przez polskie kluby piłkarskie. Jakość usług sportowych należy utożsamić ze zdolnością do zaspokojenia potrzeb związanych z daną aktywnością fizyczną. Za pomocą metody on-line survey przeprowadzono badania ankietowe uzyskując odpowiedzi od prawie trzystu kibiców piłki nożnej. Wyniki wykazały, że typowy kibic piłki nożnej to mężczyzna w wieku od 21 do 30 lat z średnim wykształceniem i dochodem poniżej 1600 zł brutto. Z kolei jakość zbadanych działań realizowanych przez polskie kluby jest oceniana na poziomie dostatecznym. Procesowi doskonalenia powinna zostać poddana strona internetowa drużyny i asortyment pamiątek klubowych. Organizacje sportowe chcąc pozyskać większą liczbę stałych kibiców powinny realizować swoje działania marketingowe na podstawie cyklicznych badań potrzeb i oczekiwań kibiców. Słowa kluczowe: kibic, piłka nożna, klub piłkarski, widowisko sportowe, jakość usług, segmentacja, marketing sportu. Abstract Fans are the essence of the sports event and their absence in the stands can negatively affect on the value of events, which are evaluated from the perspective of permanent fans, sponsors and media. The main objective of the study was the assessment of the quality of selected services offered by Polish football clubs. The quality of sports services should be defined as the ability to meet the needs of a particular physical activity. By means of on-line survey method was conducted research, receiving responses from nearly three hundred football fans. The results showed that the fan of football is the man between 21 and 30 years of age with secondary education and gross income below 1600 PLN. The quality of examined the activities carry out by the Polish clubs is judged on passable level. The process of improvement should be start with the team website and the assortment of football souvenirs. Sports organizations in order to attract more permanent fans should realize their marketing efforts by regular research of needs and expectations of fans. Key words: fan, football, football club, sports event, quality of services, segmentation, sports marketing. [1] e-mail: a.dziegiel@o2.pl [2] e-mail: l.lucinski@gmail.com